2018
DOI: 10.1002/chem.201705790
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nanowheels with Axles Containing Noble Gas Atoms: Viable Noble Gas Bound M©B10Clusters (M=Nb, Ta)

Abstract: The viability of noble gas axled boron nanowheels Ng M©B (Ng=Ar-Rn; M=Nb, Ta; n=1, 2) is explored by ab initio computations. In the resulting Ng -M complexes, the Ng-M-Ng nanorod passes through the center of the B ring, providing them with an inverse sandwich-like structure. While in the singly Ng bound analogue, the Ng binding enthalpy H at 298 K ranges from 2.5 to 10.6 kcal mol , in doubly Ng bound cases it becomes very low for the Ng M©B →Ng+NgM©B dissociation channel, except for the case of Rn, for which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Subsequently, on a laboratory scale, a variety of compounds possessing Ng‐Halogen, [ 2,11–14 ] ‐oxygen, [ 15 ] ‐sulfur, [ 16 ] ‐nitrogen, [ 17–21 ] among others, [ 22,23 ] bonds have been obtained at extreme conditions, and theoretically studied through high‐level calculations. [ 24–31 ] Those findings were even more surprising when it was realized that these compounds can form covalent bonds with other atoms, going contrary to what has been believed about the noble gas behavior. Recently, interest has grown in the study of Ng‐compounds because they were found in the interstellar medium.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Subsequently, on a laboratory scale, a variety of compounds possessing Ng‐Halogen, [ 2,11–14 ] ‐oxygen, [ 15 ] ‐sulfur, [ 16 ] ‐nitrogen, [ 17–21 ] among others, [ 22,23 ] bonds have been obtained at extreme conditions, and theoretically studied through high‐level calculations. [ 24–31 ] Those findings were even more surprising when it was realized that these compounds can form covalent bonds with other atoms, going contrary to what has been believed about the noble gas behavior. Recently, interest has grown in the study of Ng‐compounds because they were found in the interstellar medium.…”
Section: Introductionmentioning
confidence: 89%
“…[44] This level of theory has proven to be sufficient for a proper analysis of the chemical bond nature. [26,29,31] EDA procedure takes interaction energy (ΔE int ) and decomposes it in three principal energy terms, which describe the type of interaction between the atoms: The electrostatic interaction energy (ΔE elstat ), Pauli repulsion energy (ΔE Pauli ) and orbital interaction energy (ΔE orb ). In this analysis, scalar relativistic effects were considered for heavier atoms (I, Xe and Rn) using zeroth-order regular approximation [45,46] (ZORA).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the introduction of heteroatoms in boron clusters has created a variety of intriguing doped boron clusters, including metal-centered monocyclic ring/tubular/cage structures, (Romanescu et al, 2011;Jian et al, 2016;Dong et al, 2018;Liang et al, 2018;Chen et al, 2019;Lu et al, 2021), half-sandwich structures, (Chen et al, 2018;Ren et al, 2019), inverse sandwich structures, (Cui et al, 2020;Jiang et al, 2021), metallo-borophenes (Li et al, 2016;Zhang et al, 2016) and metallo-borospherenes, (Chen et al, 2020;Zhang et al, 2021), strongly leading to a new direction of research on boron chemistry and pushing the limit of structural chemistry as well as the record of coordination number in 2D and 3D environments for central metal atoms. (Islas et al, 2007;Liu et al, 2007;Miao et al, 2009;Popov et al, 2014;Pan et al, 2018;Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This discovery opened a new chapter in the Ng chemistry refuting the prejudice regarding the chemical inertness of Ngs. After this finding, a vast series of Ng compounds were either characterized experimentally or predicted to be viable in silico (Thompson and Andrews, 1994 ; Pettersson et al, 1995 , 1997 , 1998a , b ; Evans and Gerry, 2000a , b ; Evans et al, 2000a , b ; Khriachtchev et al, 2000 , 2001 , 2003a , b ; Li et al, 2002 ; Feldman et al, 2003 ; Tanskanen et al, 2003 ; Cooke and Gerry, 2004a , b ; Wang et al, 2004 , 2012 ; Smith et al, 2007 ; Chakraborty et al, 2010 ; Pan et al, 2013a , b , 2014 ; Debackere et al, 2014 ; Khatua et al, 2014 ; Mondal and Chattaraj, 2014 ; Chakraborty and Chattaraj, 2015a , b ; Pan et al, 2015a , b , c , d , 2016a , b , 2018a , b ; Saha et al, 2015 , 2016 , 2017 , 2019 ; Jana et al, 2018a ). Similarly, the noble metals (M = Cu, Ag, Au) are known to be comparatively less reactive that allows their use in day-to-day life.…”
Section: Introductionmentioning
confidence: 99%